Precursors of exhausted T cells are pre-emptively formed in acute infection - Talyn Chu; Ming Wu; Barbara Hoellbacher; Gustavo P. de Almeida; Christine Wurmser; Jacqueline Berner; Lara V. Donhauser; Ann-Katrin Gerullis; Siran Lin; J. Diego Cepeda-Mayorga; Iman I. Kilb; Lukas Bongers; et al. (Nature, 2025)
Abstract T cell exhaustion limits effector T cell function in chronic infection and tumours1,2. The development of these hypofunctional T cells and of their precursors was considered to require stimulatory conditions that are met only after persistent exposure to antigen and inflammation. Here we show, however, that similar T cell populations exist in the early phase of acute infections1,2. At that stage, the early developing TCF1+ precursor population exhibits an unexpected diversity; it includes precursors of normal memory T cells, but also cells with phenotypic, gene-expression and epigenetic profiles that resemble those of precursors of exhausted T cells found in chronic infections. We show that high ligand affinity promotes and PD-1 signalling restricts the development of these precursors. Although the exhausted precursors are at first found frequently, they decline without being completely lost in infections that the immune system resolves. We therefore conclude that precursor T cells with at least two distinct phenotypes are pre-emptively generated irrespective of the outcome of an infection.